2013
DOI: 10.1016/j.ympev.2013.04.030
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and biogeography of the austral horse fly tribe Scionini (Diptera: Tabanidae: Pangoniinae) inferred from multiple mitochondrial and nuclear genes

Abstract: Phylogenetic relationships within the Tabanidae are largely unknown, despite their considerable medical and ecological importance. The first robust phylogenetic hypothesis for the horse fly tribe Scionini is provided, completing the systematic placement of all tribes in the subfamily Pangoniinae. The Scionini consists of seven mostly southern hemisphere genera distributed in Australia, New Guinea, New Zealand and South America. A 5757 bp alignment of 6 genes, including mitochondrial (COI and COII), ribosomal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 48 publications
5
42
0
Order By: Relevance
“…More recently, Almeida et al (2012) demonstrated that the latest cladogeneses between South American and Australian elements of colletid bees occurred about 30 million years ago. This was later corroborated with results in scionini tabanid evolution (Lessard et al, 2013).…”
Section: Biogeographical and Evolutionary Implicationssupporting
confidence: 84%
“…More recently, Almeida et al (2012) demonstrated that the latest cladogeneses between South American and Australian elements of colletid bees occurred about 30 million years ago. This was later corroborated with results in scionini tabanid evolution (Lessard et al, 2013).…”
Section: Biogeographical and Evolutionary Implicationssupporting
confidence: 84%
“…PCR used primers (all at 10nmol/µl) previously published or designed for this study (Supplementary Table 2) and reactions used TaKaRa Ex Taq (Takara Bio, Shiga, Japan) following manufacturer's recommendations and the protocol of Lessard et al (2013). In PCR for CO1, 1µl of primer and 0.8µl of DNA were used, and for nuclear genes, 2µl of primer, 1µl of DNA and 2µl of MgCl 2 , for a total volume of 49µl.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…This narrative, mixing vicariance and dispersal, has recently been suggested for other, strictly southern organisms. For example, in flies, the Pagoniinae (subfamily of Tabanidae, Lessard et al 2013), and bees, the family Colletidae (Almeida et al 2012). …”
Section: A Timeframe For Muscidae Diversificationmentioning
confidence: 99%
“…Because radiation of gingers and tabanid flies both occurred in late Cretaceous, similar to many other genera of plants and animals, their diversification toward the Indian plate is thus linked with Gondwana separation (Kress and Specht ; Lessard et al. ). Further radiation and speciation in Zingiberaceae, following the collision between Indian and Eurasian plate in the last 50 Ma, led to the evolution of long corolla tubed genus Roscoea from relatively shorter corolla tube genus Hedychium in the Himalayas (Ngamriabsakul et al.…”
Section: Introductionmentioning
confidence: 99%